Pre-eminence of determining factors in second language learning: An educators' perspective from Spain - Arigita García, Amaya; Sánchez Cabrero, Roberto; Barrientos Fernández, Amelia; Manoso Pacheco, Lidia; Pericacho Gómez, Francisco Javier (My University, 2021)
Second language acquisition as a process is subject to factors related to the student, the teacher, the learning structure and learning organisation, and also to the learning environment. The research hereby presented aims to establish the relevance of the above-mentioned factors in the process of second language learning. The study addresses the point of view of teachers, as their perspective concerning the learning process is privileged. If it were not to be included in a scientific process, this detailed and contextual knowledge would not be able to contribute to the improvement of teaching. The data obtained will allow for the designing of teaching strategies focused on learners' needs and requirements. This is a descriptive, observational and cross-sectional study with the participation of 216 practicing teachers within the Community of Madrid in Spain. The information was collected through an online questionnaire using the Google Drive tool Google Forms. Then, it was analysed and validated with IBM SPSS Statistics 25.0. The outcomes of the study show that the factors linked to the teacher are the most dominant for those educators in the Community of Madrid. Regarding the teacher-student relationship, the use of teaching resources and materials adequate for learning, together with the communication, strategies used, the linguistic input received by the students and the planning of lessons, are factors showing the greatest capacity to determine the process of teaching and learning a second language.